THE PROBLEM OF ALCOHOL DEPENDS AND THE FIGHT AGAINST IT - Mamatkulov Bakhromjon; Avezova Gulo yim Sattarovna; Tuliyev Ravsho n Rasnidovich (Scholar Express Journals, 2021)
The negative effect of alcohol is manifested in various forms both socially and medically.  The consumption of alcohol is an integral part of society even in the past, as it is now, and in the future, despite its negative consequences, it remains in the same position as it was in the past.  The article analyzes the main legislation of the Republic of Uzbekistan aimed at reducing alcoholism and combating alcoholism, as well as the formation of a healthy lifestyle.
Keywords: Alcoholism; Public Policy; Alcoholism Prophylactics; Healthy Lifestyle